2022
DOI: 10.1021/acsestengg.2c00284
|View full text |Cite
|
Sign up to set email alerts
|

Pilot-Scale Field Demonstration of Environmental Nanotechnology for Groundwater Defluoridation

Abstract: Fluoride contamination in groundwater is a global issue. Nanoscale oxides of Zr(IV), Al(III), and Ti(IV) can form the inner-sphere complex with fluoride through ligand exchange, offering a new chance for efficient groundwater purification. However, pilot-scale field demonstration of nanotechnology in groundwater defluoridation is very rare. Herein, we conducted a 150-day field defluoridation study using the nanocomposite HZO@D201, which was prepared by encapsulating nano-hydrated zirconium oxide (HZO) inside t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…Furthermore, exploring the adsorption technique as an alternative to aluminum-based coagulation for defluoridation is worthwhile, as the (hydr)oxides of tetravalent metals such as Zr(IV), Ce(IV), and Ti(IV) have been extensively reported capable of effectively reducing fluoride concentrations to below 1 mg/L. 5,64,65 ■ ASSOCIATED CONTENT * sı Supporting Information…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, exploring the adsorption technique as an alternative to aluminum-based coagulation for defluoridation is worthwhile, as the (hydr)oxides of tetravalent metals such as Zr(IV), Ce(IV), and Ti(IV) have been extensively reported capable of effectively reducing fluoride concentrations to below 1 mg/L. 5,64,65 ■ ASSOCIATED CONTENT * sı Supporting Information…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Various techniques, including adsorption, 5 coagulation, 6 chemical precipitation, 7 and membrane separation, 3 have been studied for defluoridation of industrial wastewater.…”
Section: ■ Introductionmentioning
confidence: 99%
“…6,16 Interestingly, the formation of Zr−P (l Zr−P : 2.76 Å) was rarely mentioned in the process of P adsorption, and most studies just confirmed that the Zr−O−P coordination (l Zr−O : 2.06 Å) is present on the surface of sorbents. 17 It is unclear whether Zr-based nanomaterials can form both structures in the treatment of phosphoruscontaining wastewater, and the formation process and mechanism need to be investigated. 18 The stability of the two Zr−P deserves further attention, as it affects the removal and recovery of P. This kind of study was first reported in the composites, and similar studies have confirmed that nanolanthanum hydroxide can enhance the formation of La−P structure in the confined domain.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have clarified the P removal mechanism using the Zr-based nanocomposites, in which the main contribution is the formation of complexes on the inner and outer surfaces of the adsorbent due to the strong complexation interaction of hydroxyl groups. , Interestingly, the formation of Zr–P ( l Zr–P : 2.76 Å) was rarely mentioned in the process of P adsorption, and most studies just confirmed that the Zr–O–P coordination ( l Zr–O : 2.06 Å) is present on the surface of sorbents . It is unclear whether Zr-based nanomaterials can form both structures in the treatment of phosphorus-containing wastewater, and the formation process and mechanism need to be investigated .…”
Section: Introductionmentioning
confidence: 99%